Tajikistan on its way to military and political stability - Bogdan Levyk (Cхід, 2013)
The paper reviews the military policy of a new independent Republic of Tajikistan over 1991-2011. The smallest by territory Central Asian republic lived through a five-year civil war on its way to an independent sovereign democratic state which seven million people were wise enough to reach national reconciliation in 1997. The majority of Tajikistan population is on the verge of poverty, which is indicative of the inadequate social policy. The country is rich in Pamir water which is drawn from eleven glaciers as well as cotton, electric energy and aluminum. Tajikistan secures its military power owing to cooperation with the CIS, the Collective Security Treaty Organization and the Shanghai Cooperation Organization. The Republic develops all-embracing cooperation with such Asian countries as India, Pakistan, Turkey, China and Iran. Among European countries it is Germany that allocated funds for strengthening the border with Afghanistan, which notably stands out. Cooperation with the NATO within the Partnership for Peace Program helps the military of the Republic to dispose of outdated ammunition as well as take part in NATO peacekeeping operations in accordance with resolutions of the United Nations Security Council. The Russian Federation having the largest foreign military alignment in the territory of the Republic remains the main strategic partner and guarantor of the national sovereignty of Tajikistan. The Republic still faces the problems of energy resources, terrorism and international drug trafficking. The internal political situation requires continuous international monitoring. UN observers left the country in 2000. The authoritarian government does not contribute to development of the democratic foundation of civil society. Today's Armed Forces of Tajikistan are of insignificant numerical strength and poorly-armed. The Army needs modernization and adaptation to a present-day environment.